ANALISIS HUBUNGAN ANTARA ZONA IKLIM LOKAL DAN SUHU PERMUKAAN LAHAN DI KOTA MAKASSAR - Tika, Nurhasanah; Wibowo, Adi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
The rapid expansion of built-up areas in Makassar City has led to an increase in Land Surface Temperature (LST) and intensified the Urban Heat Island (UHI) phenomenon. This study aims to analyze the relationship between Local Climate Zones (LCZ) and surface temperature distribution across three districts: Tallo, Panakkukang, and Manggala. The methods involved rule-based LCZ classification using Sentinel-2 imagery and high-resolution (10-meter) LST prediction through a Random Forest model based on Landsat 8 and Sentinel-2 data, processed in Google Earth Engine. The results indicate that built-up zones such as compact low-rise and sparsely built areas exhibit significantly higher surface temperatures compared to vegetated and water zones. These findings confirm that the spatial distribution of LCZs strongly influences urban thermal variation and highlight the importance of climate-responsive urban planning through increased green spaces and water body preservation to mitigate localized heating in Makassar City.